Pradefovir Treatment in Patients With Chronic Hepatitis B: Week 24 Results From a Multicenter, Double-Blind, Randomized, Noninferiority, Phase 2 Trial. (6th September 2021) - Gao, Yanhang; Kong, Fei; Song, Xinwen; Shang, Jia; Yao, Lvfeng; Xia, Jinyu; Peng, Yanzhong; Liu, Weidong; Gong, Huanyu; Mu, Mao; Cui, Hesong; Han, Tao; et al.
Abstract: Background: Pradefovir is a liver-targeted prodrug of adefovir, a nucleoside/nucleotide analogue with antiviral activity against hepatitis B virus (HBV) DNA polymerase. This phase 2 study compared the efficacy and safety of oral pradefovir (30, 45, 60, or 75 mg) versus tenofovir disoproxil fumarate (TDF; 300 mg) and aimed to identify the most appropriate dose of pradefovir for the forthcoming phase 3 study. Methods: Treatment-naive and experienced (not on treatment >6 months) patients with chronic hepatitis B were eligible. Results: A total of 240 participants were randomized and treated in the study (48 per group). Approximately 80% were hepatitis B e antigen (HBeAg) positive, and 10% had liver cirrhosis. The reductions from baseline in HBV DNA levels achieved at week 24 were 5.40, 5.34, 5.33, and 5.40 log10 IU/mL, with pradefovir doses of 30-, 45-, 60-, and 75-mg, respectively, compared with 5.12 log10 IU/mL with TDF. However, HBeAg loss was attained by more participants who received 45-, 60-, or 75-mg pradefovir than by those receiving TDF (12%, 6%, and 9% vs 3%). The TDF group exhibited a more significant increase in serum creatinine than the pradefovir 30- and 45-mg groups, and serum phosphate levels were comparable among all groups. Most adverse events (AEs) were mild (grade 1). No treatment-related severe AEs were reported. Overall, AEs and laboratory abnormalities were comparable to those in the TDF group. Conclusions: Pradefovir and TDF exhibited comparable reductions in HBV DNA levels. All treatments were safe and well tolerated. Clinical Trials registration: NCT00230503 and China Drug Trials CTR2018042 Abstract : In a phase 2 trial, pradefovir—a liver-targeted prodrug of adefovir, a nucleoside/nucleotide analogue with antiviral activity against hepatitis B virus (HBV) DNA—exhibited good efficacy in reducing HBV DNA levels and an acceptable safety profile, comparable to tenofovir disoproxil fumarate.